Intellegent computers − the means for automatization of scientific investigating and reliable solving of scientific and engineering problems - Molchanov, I.N.; Khimich, A.N.; Popov, A.V.; Chistyakova, T.V.; Yakovlev, M.F. (Искусственный интеллект, 2014)
The intelligent computer investigates characteristics of problem’s computer model and on the basis of this information it automatically constructs the solution algorithm, forms a topology from MIMD-computer’s processors, creates a parallel program code, solves the problem and, finally, estimates the reliability of the obtained results (the proximity between machine and mathematical solutions as well as estimate of inherited error in the obtained solution).